2022
DOI: 10.3390/brainsci12121667
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Cognitive Impairment Induced by Prenatal Alcohol Exposure

Abstract: Alcohol is one of the most commonly used illicit substances among pregnant women. Clinical and experimental studies have revealed that prenatal alcohol exposure affects fetal brain development and ultimately results in the persistent impairment of the offspring’s cognitive functions. Despite this, the rate of alcohol use among pregnant women has been progressively increasing. Various aspects of human and animal behavior, including learning and memory, are dependent on complex interactions between multiple mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 167 publications
0
1
0
Order By: Relevance
“…Nicotine is one of the primary substances that elicit dependence in cigarettes. Alhowail (2021) showed that nicotine affects cognitive development by altering the expression and function of nAChR subunits, altering ERK1/2 activity, and increasing GluR2 surface expression, as well as decreasing neurogenesis, synaptic plasticity in the hippocampus and cortex. Consistent with the above findings, this study found smoking may serve as a independent risk factor for cognitive function in middle-aged and elderly patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is one of the primary substances that elicit dependence in cigarettes. Alhowail (2021) showed that nicotine affects cognitive development by altering the expression and function of nAChR subunits, altering ERK1/2 activity, and increasing GluR2 surface expression, as well as decreasing neurogenesis, synaptic plasticity in the hippocampus and cortex. Consistent with the above findings, this study found smoking may serve as a independent risk factor for cognitive function in middle-aged and elderly patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NMDARs play a vital role to synaptic plasticity and cognitive function ( Brothwell et al, 2008 ; Suzuki et al, 2023 ). In cases of prenatal nicotine or alcohol exposure, NMDAR expression is reduced, resulting in memory deficits and impaired LTP ( Alhowail et al, 2021 ; Alhowail, 2022 ; Polli and Kohlmeier, 2022 ). Similarly, blocking NMDAR expression reduces LTP induction and results in memory impairment ( Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be extrapolated to the effects on human foetal brains and the resultant risk for neurocognitive effects with human prenatal caffeine exposure. Although experimental studies in human models may be unethical, impairments relating to memory, learning, and social development of children who were prenatally exposed to caffeine have been suggested in other studies methodologies [40][41][42].…”
Section: Caffeine's Effect On Cognition and Behaviourmentioning
confidence: 99%